Growth arrest and DNA damage‐inducible alpha regulates muscle repair and fat infiltration through ATP synthase F1 subunit alpha. Issue 1 (13th December 2022) - You, Wenjing; Liu, Shiqi; Ji, Jianfei; Ling, Defeng; Tu, Yuang; Zhou, Yanbing; Chen, Wentao; Valencak, Teresa G.; Wang, Yizhen; Shan, Tizhong
Abstract: Background: Skeletal muscle fat infiltration is a common feature during ageing, obesity and several myopathies associated with muscular dysfunction and sarcopenia. However, the regulatory mechanisms of intramuscular adipogenesis and strategies to reduce fat infiltration in muscle remain unclear. Here, we identified the growth arrest and DNA damage‐inducible alpha (GADD45A), a stress‐inducible histone folding protein, as a critical regulator of intramuscular fat (IMAT) infiltration. Methods: To explore the role of GADD45A on IMAT infiltration and muscle regeneration, the gain or loss function of GADD45A in intramuscular preadipocytes was performed. The adipocyte‐specific GADD45A knock‐in (KI) mice and high IMAT‐infiltrated muscle model by glycerol injection (50 μL of 50% v /v GLY) were generated. RNA‐sequencing, histological changes, gene expression, lipid metabolism, mitochondrial function and the effect of dietary factor epigallocatechin‐3‐gallate (EGCG) treatment (100 mg/kg) on IMAT infiltration were studied. Results: The unbiased transcriptomics data analysis indicated that GADD45A expression positively correlates with IMAT infiltration and muscle metabolic disorders in humans (correlation: young vs. aged people, Gadd45a and Cebpa, r 2 = 0.20, P < 0.05) and animals (correlation: wild‐type [WT] vs. mdx mice, Gadd45a and Cebpa, r 2 = 0.38, P < 0.05; NaCl vs. GLY mice, Gadd45a and Adipoq/Fabp4, r 2 = 0.80/0.71, both P < 0.0001). In vitro, GADD45A overexpression promotes intramuscular preadipocyte adipogenesis, upregulating the expression of adipogenic genes ( Ppara : +47%, Adipoq : +28%, P < 0.001; Cebpa : +135%, Fabp4 : +16%, P < 0.01; Pparg : +66%, Leptin : +77%, P < 0.05). GADD45A knockdown robustly decreased lipid accumulation ( Pparg : −57%, Adipoq : −35%, P < 0.001; Fabp4 : −37%, P < 0.01; Leptin : −28%, P < 0.05). GADD45A KI mice exhibit inhibited skeletal muscle regeneration (myofibres: −40%, P < 0.01) and enhanced IMAT infiltration (adipocytes: +20%, P < 0.05). These KI mice have impaired exercise endurance and mitochondrial function. Mechanistically, GADD45A affects ATP synthase F1 subunit alpha (ATP5A1) ubiquitination degradation (ubiquitinated ATP5A1, P < 0.001) by recruiting the E3 ubiquitin ligase TRIM25, which decreases ATP synthesis (ATP production: −23%, P < 0.01) and inactivates the cAMP/PKA/LKB1 signalling pathway (cAMP: −36%, P < 0.01; decreased phospho‐PKA and phospho‐LKB1 protein content, P < 0.01). The dietary factor EGCG can protect against muscle fat infiltration (triglyceride: −64%, P < 0.05) via downregulating GADD45A (decreased GADD45A protein content, P < 0.001). Conclusions: Our findings reveal a crucial role of GADD45A in regulating muscle repair and fat infiltration and suggest that inhibition of GADD45A by EGCG might be a potential strategy to combat fat infiltration and its associated muscle dysfunction.